2005
DOI: 10.1007/s10751-005-9151-y
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Nanoparticles

Abstract: Semiconductor nanoparticles exhibit size dependent properties, when their size is comparable to the size of Bohr diameter for exciton. This can be exploited to increase fluorescence efficiency or increase the internal magnetic field strength in doped semiconductors. Nanoparticles are usually unstable and can aggregate. It is therefore necessary to protect them. Surface passivation using capping molecules or by making coreYshell particles are some useful ways. Here synthesis and results on doped and un-doped na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Among nanomaterials, the semiconductor nanoparticles (NPs) have attracted a great deal of attention due to their size dependent intense optical properties [4,5]. The quantum confinement phenomenon has been utilized to tune the optical properties of quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…Among nanomaterials, the semiconductor nanoparticles (NPs) have attracted a great deal of attention due to their size dependent intense optical properties [4,5]. The quantum confinement phenomenon has been utilized to tune the optical properties of quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectrum is given in figures 1 and figure 2. UV Spectrometric analysis showed that as particle size is reduced below the Bohr size of exciton, the energy gap increases and can be observed as shift in the absorption edge (Bangal and Ashtaputre, 2005). Band gaps for Zinc Sulfide (with and without CTAB) were 5.48 eV and 5.99 eV, respectively which was much increased from band gap for bulk ZnS (3.68 eV).…”
Section: Resultsmentioning
confidence: 97%
“…Transmission electron microscopy (TEM, model: LEO 912AB-Germany) and scanning electron microscopy (SEM, model: LEO 1450VP-Germany) were used to www.pss-c.com physica p s s status solidi c determine the particle size and morphology of nanopowders. Optical characterizations were carried out by Fourier transform infra red spectroscopy from reflectance spectra of powders in KBr matrix in the region (400-4000 cm −1 ) and also by UV absorbance spectra from nanopowders ultrasonically dispersed in distilled water were recorded as discussed by Bangal et al [13].…”
Section: Methodsmentioning
confidence: 99%